1973
DOI: 10.1507/endocrj1954.20.505
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic TSH (hCTSH, hCT) during Normal or Molar Pregnancy

Abstract: SynopsisUsing a purified human chorionic TSH (hCTSH), which was extracted from the term placenta, the authors developed a method of radioimmunoassay of hCTSH and estimated serum hCTSH in normal or molar pregnancy along with estimations of pituitary TSH (hPTSH), total thyroxine (T4) and effective thyroxine ratio (ETR). As a result, hPTSH level remained within the non-pregnant range throughout the whole course of pregnancy, but hCTSH tended to increase gradually toward the terminal stage of pregnancy. T4 and ETR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Although our present bioassay data are similar to their data, the RIA measurements of hCT by a method similar to that of Hennen et al do not confirm their result. Tojo et al reported finding large amounts of hCT in pregnancy sera by a specific hCT RIA, with the amount increasing during pregnancy to peak levels equivalent to about 6000 jiiU/ml at term (5). These levels, which should have been readily measurable by TSH bioassay, would probably cause overt hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Although our present bioassay data are similar to their data, the RIA measurements of hCT by a method similar to that of Hennen et al do not confirm their result. Tojo et al reported finding large amounts of hCT in pregnancy sera by a specific hCT RIA, with the amount increasing during pregnancy to peak levels equivalent to about 6000 jiiU/ml at term (5). These levels, which should have been readily measurable by TSH bioassay, would probably cause overt hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancy, a dramatic change in the release of various hormones is observed not only in the hypothalamo-pituitary-gonadal system but also in the placenta. In humans, the placenta produces numerous hormones and growth factors, including human CG (hCG), human placental lactogen (hPL), progesterone (P4), estrogens (estradiol, estrone, estriol, and estetrol) (32,33), specific pregnancy j31 glycoprotein (SP1) (34), renin (35), human chorionic corticotropin (36), human chorionic TSH (37), human chorionic FSH, human uterotropic placental hormone (38), placental LH-releasing factor (39), TSHreleasing factor (40), somatostatin-like substance (41), human nerve growth factor (42), epidermal growth factor (EGF) (43), TGFs (43,44), and insulin-like growth factors (IGFs) (45). Recently, it was found that the placenta also produces cytokines such as interleukin-1 and interleukin-6, which stimulate hCG secretion in trophoblast cells (46)(47)(48)(49)(50).…”
Section: A the Production Of Placental Hormones In Pregnancymentioning
confidence: 99%
“…This protein hormone is called human chorionic thyrotropin (HCT) and we reported on its biological, biochemical and immunological characters in 1972 (4,5). We demonstrated that the serum HCT level, estimated with our radioimmunoassay using 1311-HCT and anti-HCT serum, increased progressively during pregnancy (6) and that the progressive elevation of thyroid function during pregnancy was due not to estrogen, but to HCT originating from the placenta (7). and found them similar to those in women with normal pregnancy, but to a more extreme degree.…”
mentioning
confidence: 56%